(untitled) (Italiano LinguaDue, 2023)
Il presente contributo intende fornire un quadro di analisi sulla didattica delle lingue minoritarie nella prospettiva dell’educazione plurilingue. L’apprendimento delle lingue di minoranza contribuisce ad arricchire la dimensione del plurilinguismo in linea con le principali Raccomandazioni europee volte a riconoscere, garantire e valorizzare la diversità linguistica e culturale. Partendo dalle più significative disposizioni in materia di tutela e salvaguardia delle lingue di minoranza all’interno del contesto europeo e passando attraverso la legislazione nazionale della legge 482/1999, il contributo indaga le principali questioni (approcci e modelli) legate alle pratiche didattiche delle lingue minoritarie come strumento di educazione e pianificazione linguistica. What teaching for minority languages? Approaches and models for multilingual education This paper aims to provide a framework of analysis on teaching minority languages from the perspective of multilingual education. Minority language learning contributes to enriching the dimension of multilingualism in line with the main European Recommendations aimed at recognizing, guaranteeing, and enhancing linguistic and cultural diversity. Starting from the most significant provisions on the protection and preservation of minority languages within the European context and moving through the national legislation of Law 482/1999, the paper investigates the main issues (approaches and models) related to minority language teaching practices as a tool for language education and planning.